Penis-Sparing Surgery with Neo-Glans Reconstruction for Benign, Premalignant or Malignant Penile Lesions - Palminteri, Enzo; Fusco, Fernando; Berdondini, Elisa; Salonia, Andrea (IntechOpen, 2011)
None